Infinitely Many Nontrivial Solutions of Resonant Cooperative Elliptic Systems with Superlinear Terms - Guanwei Chen; Shiwang Ma (Abstract and Applied Analysis)
We study a class of resonant cooperative elliptic systems and replace the Ambrosetti-Rabinowitz superlinear condition with general superlinear conditions. We obtain ground state solutions and infinitely many nontrivial solutions of this system by a generalized Nehari manifold method developed recently by Szulkin and Weth.